INDONESIAN DEMOCRACY BEYOND 2024: Coalitional Presidentialism, Presidentialization, and Imperial Presidency - Hanan, Djayadi (CosmoGov: Jurnal Ilmu Pemerintahan, 2025)
During the presidency of Joko Widodo (2014 - 2024), particularly in his second term, Indonesia’s multiparty presidential democracy has witnessed the rise of an "Imperial Presidency." Coined for the first time by American historian Arthur M. Schlesinger, Jr., in his 1973 book of the same name, this term refers to a president becoming disproportionately powerful and dominant in politics and policymaking. Unlike the US, an imperial president in Indonesia does not face significant opposition from political parties or from the legislature. The existing scholarship has not sufficiently explained why an executive seeks to become dominant even when it does not face a hostile legislature. To understand how Indonesia’s imperial presidency arises, whether it will continue under Jokowi’s successor, and its potential impact on democracy, this article employs three key concepts from comparative politics: coalitional presidentialism, presidential majoritarianism, and the presidentialization of politics. Using the qualitative approach and secondary data analysis, this article argues that without significant opposition from the political parties (legislature), the judiciary, and the public, Indonesia’s imperial presidency is likely to continue and will further erode Indonesian democracy.gb777